2021
DOI: 10.1094/mpmi-01-21-0014-fi
|View full text |Cite
|
Sign up to set email alerts
|

A Seed Mucilage-Degrading Fungus From the Rhizosphere Strengthens the Plant-Soil-Microbe Continuum and Potentially Regulates Root Nutrients of a Cold Desert Shrub

Abstract: Seed mucilage plays important roles in the adaptation of desert plants to the stressful environment. Artemisia sphaerocephala is an important pioneer plant in the Central Asian cold desert, and it produces a large quantity of seed mucilage. Seed mucilage of A. sphaerocephala can be degraded by soil microbes, but it is unknown which microorganism(s) can degrade mucilage or how the mucilage-degrading microorganisms affect rhizosphere microbial communities or root nutrients. Here, mucilage-degrading microorganism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Artemisia sphaerocephala, a remarkable plant of Asian cold deserts, was used in a study where mucilage-degrading microbes were isolated from the root-soil junction. From the study, it becomes evident that the MDF associated with the roots of A. sphaerocephala recruit bacterial groups like Actinobacteria, Firmicutes, Proteobacteria, and Verrucomicrobia towards the roots and regulate the rhizosphere microbiota (Hu et al, 2021). Further, microfluidics-based investigation for real-time study of plant-microbe interaction revealed that Bacillus subtilis exhibits chemotactic behaviour towards the root elongation zone, which might be due to the secretion of root exudates (Massalha et al, 2017;Sasse et al, 2018).…”
Section: Diverse Role Of Root Exudates and Biotic Factors In Shaping ...mentioning
confidence: 96%
“…Artemisia sphaerocephala, a remarkable plant of Asian cold deserts, was used in a study where mucilage-degrading microbes were isolated from the root-soil junction. From the study, it becomes evident that the MDF associated with the roots of A. sphaerocephala recruit bacterial groups like Actinobacteria, Firmicutes, Proteobacteria, and Verrucomicrobia towards the roots and regulate the rhizosphere microbiota (Hu et al, 2021). Further, microfluidics-based investigation for real-time study of plant-microbe interaction revealed that Bacillus subtilis exhibits chemotactic behaviour towards the root elongation zone, which might be due to the secretion of root exudates (Massalha et al, 2017;Sasse et al, 2018).…”
Section: Diverse Role Of Root Exudates and Biotic Factors In Shaping ...mentioning
confidence: 96%